Minat Transaksi Daring Melalui Jasa Transportasi GO-JEK: Kepercayaan, Kemudahan Transaksional, Pemahaman Risiko Dan Kualitas Layanan - Sari, Shinta Permata; Pinandita, Satria; Sholikhah, Himmatus (Prosiding University Research Colloquium, 2019)
The ease of internet use makes all activities more efficient to accomplish. Customers can fulfill their needs by utilizing online application. The purpose of this study is to find out the effect of trust, transactional ease, risk understanding and service quality to online- transaction interest. GO-JEK’s online transportation become the observed entity because GO-JEK is one of fast growth local company in Indonesia. The study is conducted on the students at Economic and Business Faculty of Universitas Muhammadiyah Surakarta. The sampling methods of this study is convienence sampling methods. Data are collected by survey with questionnaires. 304 students are being respondents in this study. The data analyze using multiple linear regression and the results show that trust and transactional ease have effect on online-transaction interest, whereas risk understanding and service quality have no effect on online- transaction interest.